Removal of 17β-Estradiol from water by adsorption onto montmorillonite-carbon hybrids derived from pyrolysis carbonization of carboxymethyl cellulose. (15th April 2019) - Liu, Shaobo; Liu, Yunguo; Jiang, Luhua; Zeng, Guangming; Li, Ya; Zeng, Zhiwei; Wang, Xiaohua; Ning, Qimeng
Abstract: In this work, we demonstrated the preparation of the carbonized montmorillonite/carboxymethyl cellulose (MMT/CMC) hybrids and their application as an adsorbent for efficient removal of 17β-Estradiol (βE2). X-ray diffractometer (XRD) results showed that CMC intercalation reached saturation at a CMC to MMT weight ratio of 1; transmission electron microscope (TEM) measurements clearly revealed that carbonization caused graphenes distribute on the MMT surfaces; pyrolysis temperature at 600 °C yielded novel MMT/CMC sample of high surface areas as reflected by Brunauer-Emmett-Teller (BET) surface area. The adsorbed amount of βE2 under various conditions decreased in the order MMT/CMC1:1 (600) > MMT/CMC1:1 (450) > MMT/CMC1:1 (300) ∼ MMT/CMC2:1 (600) ∼ MMT > MMT/CMC5:1 (600). The removal of βE2 by MMT/CMC1:1 (600) occurred very quickly, and the adsorption kinetics could be well fitted by the Ritchie nth-order kinetic model; the best-fit adsorption isotherm model was Freundlich model. The MMT/CMC1:1 (600) also exhibited good regeneration performance after five adsorption/desorption cycles. The experimental results also showed that the adsorption of βE2 on the MMT/CMC1:1 (600) composite could contribute to hydrophobic partitioning, π−π staking interaction, H-bond interaction, pore-filling effect and simple van der Waals interaction. This highly effective and novel adsorbent can be easily synthesized and regenerated, indicating its great potential in drinking and wastewater purification for endocrine disruptor compounds. Highlights: The carbonized montmorillonite/carboxymethyl cellulose hybrid was prepared. The prepared MMT/CMC1:1 (600) showed high surface area and well-developed porosity. The adsorption property was characterized by kinetics and isotherm analysis.